Rekonsiderasi Budaya Manumbai Masyarakat Petalangan Melayu Riau Berbasis Al-Qur’an: Februari - Miftah Ulya (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2021)
Manumbai is a tradition of taking honey bee that is familiar to the people of Riau Malay Petalangan. In their view there remains a facet of inner strength, a power which cannot be reached by external effort. The unseen inner strength is greater than the outer strength. Therefore, doing a job with physical strength alone will not be sufficient, without being equipped with the effort to obtain supernatural inner strength. It has been popular that "Malay is synonymous with Islam" is a slogan that has been popular among the Riau Malay community. Even so, there still seems to be a discrepancy from what was popularized in the slogan. The author found that the manumbai procession (the ceremony for taking honey bees) in the culture of the Riau Malay Petalangan community seems to contradict the prohibitions in the al-Qur'an which are contained in the QS. Al-Nisa>'[4]: 171, namely' al-ghuluww "means transgressing the limit. This research uses a qualitative approach. While the method of interpretation in research uses the maudhu>'i> interpretation method. The stages in this research go through three stages, namely reading and tracing the literature (primary and secondary), which then analyzes the data with a descriptive analytical frame of mind, which in the end comes a conclusion. The author gives a reconsideration of the manumbai culture of the Riau Malay Petalangan community which seems to contradict the prohibition of the al-Qur'an through transformation. The desired consideration in this research is through changing the form of worship of the sialang tree which is believed to have magical powers to trust and complete belief in Allah, who is the giver and recipient of the prayers of all his servants' requests. Keywords: Reconsideration, Manumbai, Malay Culture.